2018
DOI: 10.1111/1348-0421.12596
|View full text |Cite
|
Sign up to set email alerts
|

Association of the hypha‐related protein Pra1 and zinc transporter Zrt1 with biofilm formation by the pathogenic yeast Candida albicans

Abstract: Bloodstream infection by the pathogenic fungus Candida albicans is a major health problem. Candidemia is often associated with medical devices, which can act as substrates for biofilm development. Biofilm-related infections are relatively difficult to treat because of their resistance to antimicrobial agents. It is therefore important to explore the mechanisms of biofilm formation. Dimorphism is a major contributor to biofilm formation in C. albicans. To determine whether the hypha-related proteins Pra1 (pH-re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Interestingly, previously published results on zinc effects on Candida biofilm formation are contradictory. For example, Kurakado et al demonstrated an increase in C. albicans biofilm formation as a response to ZnSO 4 and a decrease in response to zinc chelator 81 while several others report Zn-associated biofilm inhibition [82][83][84] . These contradictions could be partly due to different average (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previously published results on zinc effects on Candida biofilm formation are contradictory. For example, Kurakado et al demonstrated an increase in C. albicans biofilm formation as a response to ZnSO 4 and a decrease in response to zinc chelator 81 while several others report Zn-associated biofilm inhibition [82][83][84] . These contradictions could be partly due to different average (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In C. albicans, zinc is important in terms of both biofilm development and maintenance. The expression of genes related to zinc acquisition increases in biofilm cells of C. albicans [14,18]. Our previous report suggested that C. albicans biofilm formation is regulated by zinc and that TPEN inhibits biofilm formation [14].…”
Section: Discussionmentioning
confidence: 92%
“…The expression of genes related to zinc acquisition increases in biofilm cells of C. albicans [14,18]. Our previous report suggested that C. albicans biofilm formation is regulated by zinc and that TPEN inhibits biofilm formation [14]. Depletion of divalent cations, such as iron, calcium, and magnesium, inhibit biofilm formation by Aspergillus fumigatus and Cryptococcus neoformans [19,20].…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations